Good dispensing practices per unit dose at the Zacarías Correa Valdivia Regional Hospital in Huancavelica - Ñahui Paitan, Mery (2020)
Objective: To determine the good dispensing practices per unit dose at the Zacarías Correa Valdivia Regional Hospital in Huancavelica (HRZCVH). Material and Methods: Scientific methodology, with a basic approach, descriptive level and non-experimental, transversal and descriptive design. The sample consisted of 11 pharmaceutical professionals from HRZCVH. A “BPDDUMP” questionnaire was used, which was designed and validated by expert judgment. Results: Of the total of HRZCVH professionals, more than half (54.55%) of QM,confirm that the prescription does not meet the required data, have difficulty understanding the medical prescription, and indicate that medical prescriptions do not have legible letters and clear. 36.36% of Q. F. do not update the pharmacotherapeutic profile and 54.55% do not perform verification and monitoring of the patient’s location. 45.55% of the Q. F., indicate that the single dose boxes are not correctly identified and 18.18% do not review and corroborate the medication deposited in each box. 27.27% of Q. F., indicate that the prepared dose of a patient has been insufficient in 24 hours. And 54.55% have noticed insufficient pharmaceutical products that in an emergency and / or emergency, and only 36.36% of Q. F. have a medicine box or other reserve products for each patient. 27.27% of Q.F. confirm that there is no strict control at the time of delivery of medications and other products; and 36.36%, for narcotics. 36.36% of Q.F. confirm that the administration of the medication is not given at the exact time. Confirming by 54.55%, who have observed difficulties in meeting the time of administration of the unit dose, ratifying with 63.64% that does not observe strict compliance, in terms of the frequency of administration of the drug to each patient. Conclusions: The existence of difficulties in the dispensing process per unit dose was verified according to compliance with the Technical Standard of the Ministry of Health. This limits the good dispensing practices per unit dose at the Zacarías Correa Valdivia Regional Hospital in Huancavelica.